Diagnosis: exhaustion. (Journal of Parents and Teachers, 2014)
This article relates the situation of a teacher away from school due to exhaustion. His fundamental question: that it is useful for boys to ask and study if the system does not look at them.
Keywords: Testimony; exhaustion; tired teacher.